What Are We Studying? An overview of HCI’s curricula in Brazilian Software Engineering Undergraduate Programs - Braga Medeiros, Bruno; Felipe P. Cheiran, Jean (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
Studying and applying Human-Computer Interaction (HCI) concepts on Software Engineering (SE) programs is meaningful when society demands more useful, accessible and pleasant software applications to be made. However, teaching HCI is perceived as a challenging task in an interdisciplinary aspect. Therefore, this study aims to understand what Brazilian SE undergraduate students are being taught on HCI courses. In order to accomplish it, we applied a content analysis methodology on 21 distinct syllabi from 15 universities, which resulted on the categorization of 28 teaching topics. The outcome of this work allow us to visualize the most HCI concepts seen on Brazilian SE programs: Design, Interaction Styles & Paradigms, System Evaluation, and Usability. Moreover, we presented discussions related to the HCI knowledge being offered on SE undergraduate programs.